PENGARUH FINANCIAL STABILITY, FINANCIAL TARGETS, DAN EXTERNAL PRESSURE TERHADAP FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2017-2021 - Rumapea, Melanthon; Simanjuntak , Natasya Veronica; Silitonga, Ivo Maelina; Ginting, Mitha Christina (Journal Accounting International Mount Hope, 2024)
This study aims to test and analyze the variables of Financial Stability, Financial Targets and External Pressure which partially or simultaneously affect Financial Statement Fraud. The population in this study was 38 manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021. Determination of the sample used in this study is by purposive sampling technique totaling 16 companies with five years of observation and the data used is secondary data sourced from the company's financial and annual reports through the site www.idx.co.id. The data analysis technique used in this study is multiple linear regression analysis. The results in this study partially show that the variables Financial Stability and External Pressure have a negative and insignificant effect on Financial Statement Fraud, while Financial Targets have a positive and significant effect on Financial Statement Fraud. Simultaneously testing, the three independent variables have a significant effect on Financial Statement Fraud by 12.3%.